Effects of low-level laser therapy on reducing pain, edema, and trismus after orthognathic surgery: a systematic review - Meneses-Santos, Daniela; Costa, Marcelo D. M. A.; Inocêncio, Gabriel S. G.; Almeida, Arthur C.; Vieira, Walbert A.; Lima, Igor F. P.; Paranhos, Luiz R. (Lasers in medical science, 2022)
The purpose of this study was to systematically review the scientific evidence of the effect of low-level laser therapy (LLLT) on the perception of pain, edema, and trismus after orthognathic surgery. The literature was searched in 11 databases (MedLine via PubMed, Scopus, LILACS, SciELO, Embase, Web of Science, Cochrane Library, and LIVIVO, OpenGrey, OADT, and OpenThesis), without restriction of publication year or language. This search aimed to identify randomized clinical trials comparing low-level laser therapy and placebo for controlling pain, edema, and trismus after orthognathic surgeries. Two reviewers extracted the data and assessed the individual risk of bias of the eligible studies using the Cochrane Collaboration Risk of Bias Tool (RoB, version 2.0). The initial search resulted in 808 articles, from which only five (total of 190 participants) were included in the qualitative synthesis. The studies were published from 2014 to 2020. Two presented a low risk of bias + in the mean mouth opening of all patients subjected to bimaxillary surgery who received LLLT. However, the other study found a significant difference in maximum mouth opening in the LLLT group at 14, 30, and 60 days after surgery. Based on limited evidence, LLLT was presented as an auxiliary tool for reducing pain and trismus after surgery. However, the reduction of edema is controversial due to the absence of measuring standardization.